Effect of preoperative functional exercise on cephalic vein diameter, anastomotic blood flow, and postoperative complications in patients with arteriovenous internal fistuloplasty - Zhang, Juan; Sun, Wei; Wang, Tingting; Li, Jie; Yu, Min (Journal of the Pakistan Medical Association, 2023)
The purpose of this study was to investigate the effect of preoperative functional exercise on cephalic vein diameter, anastomotic blood flow, and postoperative complications in patients with arteriovenous internal fistuloplasty. A total of 140 patients who underwent arteriovenous fistuloplasty from March 2019 to October 2021 were randomly divided into two groups: intervention group (n=70) and control group (n=70). The control group was treated with routine nursing intervention, while the intervention group was treated with preoperative functional exercise and routine nursing intervention. There was no significant difference in the diameter of cephalic vein between the two groups two weeks before the operation (p=0.742). —Continue